Elastic and plastic deformation of surface asperities and their load-carrying mechanisms during the formation of a real contact area. (February 2023) - Kalin, M.; Zugelj, B.; Lamut, M.; Hamouda, K.
Abstract: How the contact behaviours of steel engineering surfaces with different roughnesses ( R a = 0.1, 0.6 and 1.0 µm) are affected by the asperity work-hardening and the deformation regime are described here. Large values of the plasticity index Ψ between 20 and 50 indicate that all the surfaces should undergo a full plastic deformation. However, in the loading range up to the yield stress (on a nominal contact area) the rough surfaces exhibited at least 10 % elastic deformation, while for the smooth surfaces the elastic deformation was as much as 44 %. During the loading, the work-hardening increased the hardness of the rough surfaces by up to 63 %, and that of the smooth surfaces by up to 20 %. However, the asperities were able to carry the load that resulted in as much as a 4–10-times-higher contact pressure than the (initial) bulk yield strength. The proposed contact mechanisms for such an increased asperity-load-carrying capacity depend on the surface roughness. For the rough surfaces this is due to the work-hardening, while for the smooth surfaces the dominant mechanisms enhancing the load-carrying capacity are the work-hardening combined with the hydrostatic bulk stresses.